A Study of Pattern Inverted Word Order with The Same Morphemes in Chinese and Usage Problems of Thai Students - Wattanakamolkul, Pimporn (JOURNAL OF SOUTHERN TECHNOLOGY, 2024)
An inverted word order with the same morphemes refers to words that have the special characteristic of forming words with two syllables with related meanings or ones that differ from original meanings. When the word order is inverted, it results in numerous errors and confusion in word use. The objectives of this study are to: 1) analyze the patterns of word order inversion in Chinese, 2) examine the problems and errors in using word order inversion in Chinese, and 3) explore solutions for improving the teaching and learning of correct and systematic use of word order inversion in Chinese. The sample group for this research was 122 students who are third and fourth-year students from 5 universities in Thailand. The research tools consisted of inverted word order with the same morphemes in Chinese and test. Data were analyzed with frequency, percentage, t-test and One-way ANOVA. Results showed that the inverted word order with the same morphemes in Chinese can be divided into three categories based on semantic patterns. In terms of word structure, most patterns are compound words and modifiers. Regarding word function types, the majority are 'noun-noun' patterns. As for the problems and errors in using inverted word order with the same morphemes in Chinese by Thai students, they could be explained as follows. First, the understanding of word order inversion in Chinese has a correctness rate of over 50%. Second, learners have a high level of understanding of word types and categories. Third, frequently encountered words are correctly identified in terms of meaning by learners, but problematic words tend to be those that are difficult and rarely used in daily life, as well as words that retain similar original meanings. Fourth, the learners have an 83% correctness rate in using words in sentence construction. However, the average score analysis revealed that different academic years and institutions show statistically significant differences in test scores at the .05 level. The results from this study can be used to analyze and predict the problems faced by students in order to offer insights for related individuals in solving problems concerning teaching and learning activities as well as fostering effective teaching and learning practices.